(untitled) (Orinoquia, 2020)
Nostoc is a genus of filamentous cyanobacteria with biotechnological applications in human nutrition, biomedicine, biofertilization and commercial production of biofuels. However, the low growth rate in liquid medium due to its periphytic nature and its tendency to form biofilms, limits its large-scale production. Therefore, the aim of this study was to evaluate the biomass production of Nostoc muscorum in a modified hydroponic system. Cultures of N. muscorum were made by triplicate, in a hydroponic system under semicontrolled conditions of temperature (29 ± 13 °C), light intensity (32 ± 54 μmol/m2/s) and photoperiod (12 hours), for a total of 23 days inside a greenhouse. Temperature, pH, conductivity and dry biomass production were monitored on alternating days. The results showed that the maximum dry biomass production was 0.2276 ± 0.0114 g/m2/day, and the average productivity was 0.4149 ± 0.0207 g/m2/day. The maximum biomass production of N. muscorum was achieved on day thirteen with 0.3185 ± 0.0159 g/m2/day. The correlation statistical analysis of environmental variables did not show significant differences; thus, temperature, pH and electrical conductivity did not affect the biomass production of N. muscorum. Consequently, the algal growth was influenced by the species physiology only. The support used in the hydroponic system allowed the adhesion and development of the algae mucilaginous layer without requiring drying periods as in conventional crops. The hydroponic system provided a continuous flow of nutrients that could prevent the attack of opportunistic bacteria and fungi, generating a high growth rate of N. muscorum. The hydroponic system represents a viable alternative for the production of N. muscorum biomass under greenhouse conditions at large scale.